SIFAT PAPAN WOL KAYU DARI 6 JENIS KAYU HUTAN TANAMAN INDUSTRI - I M Sulastiningsih; Rodjak Memed; Paribotro Sutigno (Pusat Penelitian dan Pengembangan Hasil Hutan, 1990)
The results of laboratory test of wood wool board properties made from 6 individual wood species obtained from East Kalimantan, Jambi, South Sumatera and Maluku province are reported in this paper. The properties tested were board density, moisture content, thickness reduction due to compression and bending strength.The study reveals that average yield of wood wool is 348 kg per cubic meter of log input. The wood wool of Acacia mangium must be soaked in cold water for 24 hours prior to manufacturing of wood wool board, whereas the other species can be processed directly.The physical and mechanical properties of wood wool boards made from three wood species (Shorea platyclados, Acacia mangium and Shorea leprosulaf) catalyzed with CaCl2 solution were in conformity with the DIN 1101 standard Nevertheless, only two species (S. platyclados and A. mangium) catalyzed with Ca(OH)2 suspension met the standard requirement.